The Effect of Nutrient Fortification of Sauces on Product Stability, Sensory Properties, and Subsequent Liking by Older Adults. Issue 5 (8th April 2015) - Tsikritzi, Roussa; Wang, Jianqiu; Collins, Vanessa J.; Allen, Victoria J.; Mavrommatis, Yiannis; Moynihan, Paula J.; Gosney, Margot A.; Kennedy, Orla B.; Methven, Lisa
Abstract There are potential nutritional and sensory benefits of adding sauces to hospital meals. The aim of this study was to develop nutrient fortified sauces with acceptable sensory properties suitable for older people at risk of undernutrition. Tomato, gravy, and white sauce were fortified with macro‐ and micronutrients using food ingredients rich in energy and protein as well as vitamin and mineral premixes. Sensory profile was assessed by a trained panel. Hedonic liking of fortified compared with standard sauces was evaluated by healthy older volunteers. The fortified sauces had higher nutritional value than the conventional ones, for example the energy content of the fortified tomato, white sauce, and gravy formulations were increased between 2.5‐ and 4‐fold compared to their control formulations. Healthy older consumers preferred the fortified tomato sauce compared with unfortified. There were no significant differences in liking between the fortified and standard option for gravy. There were limitations in the extent of fortification with protein, potassium, and magnesium, as excessive inclusion resulted in bitterness, undesired flavors, or textural issues. This was particularly marked in the white sauce to the extent that their sensory characteristics were not sufficiently optimized for hedonic testing. It is proposed that the development of fortified sauces is a simple approach to improving energy intake for hospitalized older people, both through the nutrient composition of the sauce itself and due to the benefits of increasing sensorial taste and lubrication in the mouth.